2012
DOI: 10.1128/ec.00113-12
|View full text |Cite
|
Sign up to set email alerts
|

The Aspergillus fumigatus Protein GliK Protects against Oxidative Stress and Is Essential for Gliotoxin Biosynthesis

Abstract: The function of a number of genes in the gliotoxin biosynthetic cluster (gli) in Aspergillus fumigatus remains unknown. Here, we demonstrate that gliK deletion from two strains of A. fumigatus completely abolished gliotoxin biosynthesis. Furthermore, exogenous H 2 O 2 (1 mM), but not gliotoxin, significantly induced A. fumigatus gliK expression (P ‫؍‬ 0.0101). While both mutants exhibited significant sensitivity to both exogenous gliotoxin (P < 0.001) and H 2 O 2 (P < 0.01), unexpectedly, exogenous gliotoxin r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
70
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(71 citation statements)
references
References 40 publications
0
70
1
Order By: Relevance
“…This scenario is in contrast to that observed for wild-type A. fumigatus, whereby downregulation of MTHFR/MtrA was noted in response to gliotoxin and H 2 O 2 combined, relative to the solvent control (11). Although an altered GliT abundance was not detectable in the A. fumigatus ⌬gliK strain during the above-mentioned 2-DE-LC-MS/MS analysis, it has been reported that elevated gliT expression occurs in response to gliotoxin exposure in this mutant (7). Here, parallel LFQ proteomic investigations of the A. fumigatus ⌬gliK strain, in the presence and absence of gliotoxin, revealed a 14-to 15-fold (log 2 -fold change ϭ 3.837)-increased abundance of GliT, compared to the 250-fold increase in wild-type A. fumigatus following gliotoxin exposure.…”
Section: Integrated Systems In Aspergillus Fumigatuscontrasting
confidence: 45%
See 4 more Smart Citations
“…This scenario is in contrast to that observed for wild-type A. fumigatus, whereby downregulation of MTHFR/MtrA was noted in response to gliotoxin and H 2 O 2 combined, relative to the solvent control (11). Although an altered GliT abundance was not detectable in the A. fumigatus ⌬gliK strain during the above-mentioned 2-DE-LC-MS/MS analysis, it has been reported that elevated gliT expression occurs in response to gliotoxin exposure in this mutant (7). Here, parallel LFQ proteomic investigations of the A. fumigatus ⌬gliK strain, in the presence and absence of gliotoxin, revealed a 14-to 15-fold (log 2 -fold change ϭ 3.837)-increased abundance of GliT, compared to the 250-fold increase in wild-type A. fumigatus following gliotoxin exposure.…”
Section: Integrated Systems In Aspergillus Fumigatuscontrasting
confidence: 45%
“…BmGT formation in the A. fumigatus ⌬gliT strain was identically evaluated. Culture supernatants were subjected to organic extraction and liquid chromatography-mass spectrometry (LC-MS) analysis to detect gliotoxin and BmGT, as previously described (7,10). GtmA activity in the A. fumigatus ⌬gliK strain was determined as described previously for the A. fumigatus ⌬gliT strain (10).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations